Jane Eyre (1973) [videorecording (DVD)] - Craft, Joan; Cusack, Sorcha, 1949-; Jayston, Michael, 1935-; Brontë, Charlotte, 1816-1855 (Acorn Media, 2006)
An orphan cast out as a young girl by her aunt is sent to be raised in a harsh charity school for girls.